Evidence of underdiagnosis of myasthenia gravis in older people. - Vincent, A; Clover, L; Buckley, C; Grimley Evans, J; Rothwell, P (2003)
BACKGROUND: Myasthenia gravis is a potentially serious but treatable muscle disease caused by autoantibodies directed at the acetylcholine receptor (AChR) on the postsynaptic membrane of the neuromuscular junction. There is anecdotal evidence that the diagnosis is sometimes missed in older patients. OBJECTIVE: To examine the incidence and age distribution of positive AChR antibodies in samples referred to diagnostic laboratories in the UK, and the prevalence of positive AChR antibodies in samples from a cohort of older individuals. METHODS: Positive AChR antibody tests were identified from all UK centres registered for the assay with the European quality assurance scheme (EQAS) during 1997-99, and the age and sex specific incidence was calculated, based on the UK population. The prevalence of AChR antibodies in sera from a sample of 2000 individuals aged > or =60 years was determined. RESULTS: 3183 individuals had positive AChR antibody tests on routine screening during the years 1997 to 1999 in the UK, giving an annual incidence of 1.8/100 000. In both sexes, the age specific incidence rose steeply between the ages of 45 and 74, reaching 9.9/100 000 in men, and then fell, with a sharp decline above the age of 80. In the prevalence study, whereas only one serum from individuals aged 60-74 years was positive for AChR antibodies (0.12%), sera from eight individuals aged > or =75 years were positive (0.7%). Only one had a previous clinical diagnosis of myasthenia gravis but four others had histories of stroke or transient ischaemic attacks. CONCLUSIONS: The sharp fall in the incidence of clinically recognised myasthenia gravis in people over 80 years of age in our national AChR antibody incidence study, and the high prevalence of previously unrecognised positive AChR antibodies in those > or =75 years old, suggest that myasthenia gravis may be substantially underdiagnosed in older people.